Dense integration of graphene and sulfur through the soft approach for compact lithium/sulfur battery cathode. (March 2015) - Li, Hongfei; Yang, Xiaowei; Wang, Xiaomin; Liu, Meinan; Ye, Fangmin; Wang, Jin; Qiu, Yongcai; Li, Wanfei; Zhang, Yuegang
Abstract: The main challenge for the lithium/sulfur battery is the significant capacity decay over cycling, as the result of the diffusion of lithium polysulfide and volume/morphology changes of sulfur electrode. Porous graphene monoliths have been widely used to alleviate these problems with its confined frameworks of porous structures and strong mechanical property; however, bulk graphene materials were normally loosely packed, leading to the low utilization efficiency of pores and unsatisfactory frustration in suppressing polysulfide dissolution/shuttle owing to their large and highly open pores. Herein, we report the dense integration of sulfur and graphene (S-G) gel through the soft approach to prepare a compact sulfur cathode with dense but porous structure. The compact S-G structures could better increase the bonding between sulfur and graphene, immobilize sulfur and restrain the polysulfide diffusion within the more closed pores than loose counterpart, and thus achieve improved volumetric discharge capacities, high rate and long-term cycling performance. Graphical abstract: Highlights: A dense sulfur-graphene gel (S-G) with dense but porous structure was synthesized through a controllable soft approach. The soft approach could control the chemical structure of graphene and change the packing density of S-G composite. The dense S-G could present a better performance in trapping sulfur, to be a compact cathode of high-performance lithium/sulfur battery. The dense integration of graphene monoliths and other active materials through the soft approach could be promising to fabricate the dense but porous composite electrode for energy storage devices.